Pengelolaan Sumberdaya Mangrove Dengan Konsep Blue Economy Bagi Masyarakat Pesisir di Kecamatan Belakang Padang - Helmi Pratama Firmansyah; sri Rahayu (Prodi Ilmu Administrasi Negara, 2022)
The purpose of this study is an effort to apply the blue economy concept to optimize the potential of mangrove resources in improving the economy of coastal communities in the District of Back Padang. This research is motivated by the problem of misunderstanding for the community in utilizing the existing potential so that there is no looting of mangrove forests. The theory used in this discussion refers to the concept of the blue economy because it is oriented to the principle of strength and potential in the region as well as empowerment in strengthening the economy of coastal communities, this study also uses qualitative methods with descriptive research types. The results of this study indicate that the existence of the blue economy concept is able to answer in increasing knowledge and empowerment of coastal communities that the potential in mangrove forests can be processed into processed products such as syrup and crackers. In addition, it can create a central area for aquatic biotic cultivation, which can encourage the wheels of the economy for communities in coastal areas. The development of coastal areas must depart from its ecological and economic functions and the concept of Blue economy is a model in the field of economic strategy that isimplemented in coastal areas.